Controle robusto de sistemas não lineares e chaveado de sistemas lineares usando realimentação derivativa - Moreira, Manoel Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents theoretical studies that investigate the following problems: stability and control of nonlinear systems (descriptors) with time-varying and norm bounded uncertainties, polytopic uncertainties and exogenous disturbances; stability and control of continuous-time switched systems. Initially, a study on the design of static robust controllers for nonlinear sys- tems using state-derivative feedback is presented. Based on this study a control design method for nonlinear systems (descriptors) with exogenous disturbances is proposed. Finally, we pre- sent a study about switched linear control systems using state-derivative feedback. The work is based on feedback control laws of the time derivative of the state vector (derivative feedback) and a quadratic Lyapunov function (common or minimum-type piecewise). The motivation to use the state-derivative feedback (u(t) = −K x(t)) ̇ instead of the conventional feedback of the state vector x(t), is its easier implementation in some mechanical applications, for instance, in control of vibrations of mechanical systems, where sensors such as accelerometers have been used to measure the second-order derivative (acceleration) of a state variable (position) of these systems. The methodology presents sufficient conditions described by linear matrix inequa- lities (LMIs) for the synthesis of the following controllers: switched controllers K σ, for the stabilization of linear system using state-derivative feedback; and static robust controllers K, for, initially, the stabilization of nonlinear system, and then, are added to the design perfor- mance indices, such as the specification of the decay rate, constraint on output peak and on norm of the gain matrix and finally the constraint of the influence of exogenous disturbances. The inclusion of performance indices in the designs is very important, since usually only the stability is not sufficient for a suitable performance of the ...

Este trabalho apresenta estudos teóricos que investigam os seguintes problemas: estabilidade e controle de sistemas (descritores) não lineares com incertezas variantes no tempo limitadas em norma, incertezas do tipo politópicas e sujeitos a distúrbios exógenos; estabilidade e con- trole de sistemas chaveados lineares e contínuos no tempo. Inicialmente, um estudo sobre o projeto de controladores estáticos robustos para sistemas não lineares, usando a realimenta- ção da derivada do vetor de estado é apresentado. Em decorrência desse estudo, propõe-se métodos de projetos de controle para sistemas (descritores) não lineares que apresentam per- turbações exógenas. Por fim, é apresentado um estudo sobre controle chaveado de sistemas lineares usando a realimentação derivativa. Todo o trabalho é fundamentado em leis de controle por realimentação da derivada temporal do vetor de estado (realimentação derivativa) e na fun- ção quadrática de Lyapunov (comum ou por partes do tipo mínimo). A motivação em utilizar a realimentação derivativa, ou seja u(t) = −K x(t), ̇ em vez da realimentação do vetor de estado x(t) convencional, está na facilidade de implementação em algumas aplicações mecânicas, por exemplo, no controle de vibrações de sistemas mecânicos, nos quais sensores como acelerôme- tros têm sido utilizados para medir a derivada de segunda ordem (aceleração) de uma variável de estado (posição) desse sistema. A metodologia apresenta condições suficientes na forma de desigualdades matriciais lineares (LMIs, acrônimo inglês para Linear Matrix Inequalities) para a síntese dos seguintes controladores: controladores chaveados K σ, visando a estabilização de sistemas lineares utilizando a realimentação derivativa; e controladores robustos estáticos K, visando, inicialmente, a estabilização de sistemas não lineares, e em seguida, adicionam-se ao projeto índices de desempenho, tais como,...
Keywords: Realimentação (Eletronica); Desigualdades (Matemática); Controladores elétricos; Sistemas lineares; Sistemas não lineares; Automação; Feedback (Eletronics)